2014
DOI: 10.1177/0300060513505524
|View full text |Cite
|
Sign up to set email alerts
|

Capn4 mRNA level is correlated with tumour progression and clinical outcome in clear cell renal cell carcinoma

Abstract: Objective: To investigate the mRNA and protein levels of calpain small subunit-1 (Capn4) in human clear cell renal cell carcinoma (ccRCC), to analyse the relationship between Capn4 mRNA level and pathological stage of ccRCC, and to examine the potential of Capn4 as a prognostic factor in ccRCC. Methods: mRNA and protein levels of Capn4 were measured in pairs of tumour tissues and matched adjacent nontumour tissue obtained from patients with ccRCC by quantitative reverse transcription-polymerase chain reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
3
6
0
Order By: Relevance
“…Understanding the molecular mechanisms of gliomagenesis and tumor progression is necessary to explore more effective diagnostic and therapeutic strategies. In a previous study, it was shown that alterations in Capn4 expression correlated with glioma grade and patient survival (13). In the present study, we have shown that the Capn4 protein levels, but not the mRNA levels, in GBM were higher than the control tissues, which is consistent with our immunohistochemical findings in our previous report (13).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Understanding the molecular mechanisms of gliomagenesis and tumor progression is necessary to explore more effective diagnostic and therapeutic strategies. In a previous study, it was shown that alterations in Capn4 expression correlated with glioma grade and patient survival (13). In the present study, we have shown that the Capn4 protein levels, but not the mRNA levels, in GBM were higher than the control tissues, which is consistent with our immunohistochemical findings in our previous report (13).…”
Section: Discussionsupporting
confidence: 93%
“…Capn4 overexpression was observed in intrahepatic cholangiocarcinoma tissues and involved in the metastasis of intrahepatic cholangiocarcinoma (12). Higher Capn4 expression was also identified in and associated with poor overall survival (OS) of clear cell renal cell carcinoma patients (13). In a previous study, we also observed an increased expression of Capn4 in glioma tissues, which was associated with a poorer OS and progression-free survival (PFS) of GBM patients.…”
Section: Introductionmentioning
confidence: 67%
“…In tumorigenesis, the prognostic and therapeutic value of calpain-4 have been illustrated in hepatocellular carcinoma, intrahepatic cholangiocarcinoma, clear cell renal cell carcinoma, non-small cell lung cancer, nasopharyngeal carcinoma and glioma [12,13,14,15,16,17]. High calpain-4 expression is found to be positively correlated with tumor invasion and metastasis, and predicts poor prognosis in these types of malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicates that calpain-4 could regulate the organization of the actin cytoskeleton during cell migration [11]. Overexpression of calpain-4 is observed in several types of tumors, such as hepatocellular carcinoma, intrahepatic cholangiocarcinoma, and clear cell renal cell carcinoma, and could be regarded as a predictor of poor prognosis [12,13,14,15,16,17]. Nevertheless, the roles of calpain-4 in gastric carcinoma remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Calpain small subunit 1 (Capn4) is a small regulatory subunit of the Calpain family and plays a crucial role in the maintenance of calpain’s stability and activity 15. A previous study indicated that the overexpression of Capn4 was the underlying cause of invasion and metastasis after liver transplantation in hepatocellular carcinoma 16. Another study revealed that Capn4 was upregulated and was associated with tumor progression and its clinical outcome in clear cell renal cell carcinoma 17.…”
Section: Introductionmentioning
confidence: 99%